Online Music Store (OMS) / Jeyaprakash Dorairaja - Jeyaprakash, Dorairaja (2004)
The Online Music Store (OMS) is an internet/intranet-based electronic commerce system, which enables users to view, order and make transaction online. It is an application that makes use of the web's multi-tier client server architecture. The Online Music Store (OMS) can be divided into three modules, which are the customer module, administrator module and the general module. The customer module would allow customers to browse through the various CDs, which will be displayed on the online catalogue. It would provide useful tools that would enable the customers to make comparisons on the prices and features of each product. The administrator module will enable the administrator to manage the system in a more effective and systematic way. This module would enable the administrator to view, maintain and analyze the database and also update the content of the web site. The general module would enable the business to check their stock inventory before the customers confirm their order. This module would also require customers to follow certain software and hardware requirements in order to perform their transaction online. The system architecture of the Online Music Store (OMS) can be divided into client, web server and database server. The client which is the web browser can access information by connecting to the web server. Whenever, the client wants to retrieve information, it has to submit the request to the web server that will interact with the database server. The database server processes the request and the result is sent back to the web server and finally to the client. The Online Music Store (OMS) is developed using Active Server Pages (ASP) technology on the Windows NT Server platform, utilizing database created by Microsoft Access. Since current client server based database system will be transforming to web-based database system, thus the system of this nature will become essential to everyone in the future.